2022
DOI: 10.3390/nano12213759
|View full text |Cite
|
Sign up to set email alerts
|

Structure Effect on the Response of ZnGa2O4 Gas Sensor for Nitric Oxide Applications

Abstract: We fabricated a gas sensor with a wide-bandgap ZnGa2O4 (ZGO) epilayer grown on a sapphire substrate by metalorganic chemical vapor deposition. The ZGO presented (111), (222) and (333) phases demonstrated by an X-ray diffraction system. The related material characteristics were also measured by scanning electron microscopy, transmission electron microscopy and X-ray photoelectron spectroscopy. This ZGO gas sensor was used to detect nitric oxide (NO) in the parts-per-billion range. In this study, the structure e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Therefore, the potential barrier at grain boundaries enhances, resulting in the increment of resistance even further. 46 In general, the loss of electrons in sensors will increase the width of the charge depletion region, increasing its resistance, indicating that oxidizing gas will increase the resistance of n-type gas sensors. In contrast, this gas sensor demonstrated dramatically reduced response time and recovery time due to smaller grain size and grain boundaries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the potential barrier at grain boundaries enhances, resulting in the increment of resistance even further. 46 In general, the loss of electrons in sensors will increase the width of the charge depletion region, increasing its resistance, indicating that oxidizing gas will increase the resistance of n-type gas sensors. In contrast, this gas sensor demonstrated dramatically reduced response time and recovery time due to smaller grain size and grain boundaries.…”
Section: Resultsmentioning
confidence: 99%
“…Since NO molecules have a higher electron affinity (2.28 eV) than oxygen molecules (1.46 eV), they interact with adsorbed oxygen ions on the ZnO:ZnGa 2 O 4 surface. Therefore, the potential barrier at grain boundaries enhances, resulting in the increment of resistance even further . In general, the loss of electrons in sensors will increase the width of the charge depletion region, increasing its resistance, indicating that oxidizing gas will increase the resistance of n-type gas sensors.…”
Section: Resultsmentioning
confidence: 99%
“…Several gas sensors based on SMOs such as zinc oxide (ZnO), zinc gallate (ZnGa 2 O 4 ), tin oxide (SnO 2 ), nickel cobaltite (NiCo 2 O 4 ), zinc stannate (Zn 2 SnO 4 ), copper oxide (CuO), etc., possess some good properties such as precision, low cost, small dimensions, long-term stability and environmental friendliness; because of these properties, SMOs could be considered the primary candidates for the detection of toxic gases as well in photo-catalysis, etc. [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Plenty of research has shown that some complex metal oxides have been widely used as gas sensors in the last decades.…”
Section: Introductionmentioning
confidence: 99%